An advanced SEU tolerant latch based on error detection *Project supported by the National Natural Science Foundation of China (Nos. 61404001, 61306046), the Anhui Province University Natural Science Research Major Project (No. KJ2014ZD12), the Huainan Science and Technology Program (No. 2013A4011), and the National Natural Science Foundation of China (No. 61371025). (May 2018) - Xu, Hui; Zhu, Jianwei; Lu, Xiaoping; Li, Jingzhao
Abstract: This paper proposes a latch that can mitigate SEUs via an error detection circuit. The error detection circuit is hardened by a C-element and a stacked PMOS. In the hold state, a particle strikes the latch or the error detection circuit may cause a fault logic state of the circuit. The error detection circuit can detect the upset node in the latch and the fault output will be corrected. The upset node in the error detection circuit can be corrected by the C-element. The power dissipation and propagation delay of the proposed latch are analyzed by HSPICE simulations. The proposed latch consumes about 77.5% less energy and 33.1% less propagation delay than the triple modular redundancy (TMR) latch. Simulation results demonstrate that the proposed latch can mitigate SEU effectively.